2020
DOI: 10.1142/s0219519420400151
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Somatosensory Evoked Potential Patterns According to Various Vibrotactile Stimulation: Frequencies and Intensities

Abstract: This study investigates somatosensory evoked potential (SEP) patterns in the C3 somatosensory area with varying frequency and intensity of vibrotactile stimuli. The study subjects included 13 men ([Formula: see text] years) and seven women ([Formula: see text] years) who were right-handed and had normal cognitive function. The participants were subjected to three intensity levels (0.25, 0.38 and 1.3[Formula: see text]g) and eight frequencies (10, 50, 100, 150, 200, 225, 250 and 300[Formula: see text]Hz) of vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…It is concluded that the high-intensity vibration was not as clear for participants to classify as a strong vibration. Choi et al ( 2020 ) shows the difference of SEP for various frequencies and intensities. It shows that SEP peak is increased for strong stimulation, which is similar to the high P2 peak of high-intensity vibration in the ERP result of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is concluded that the high-intensity vibration was not as clear for participants to classify as a strong vibration. Choi et al ( 2020 ) shows the difference of SEP for various frequencies and intensities. It shows that SEP peak is increased for strong stimulation, which is similar to the high P2 peak of high-intensity vibration in the ERP result of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies demonstrated that vibrotactile frequency information are encoded in the P50 and P100 components of the ERP waveform in the postcentral gyrus of the primary somatosensory cortex and the parietal operculum of the secondary somatosensory cortex (Hämäläinen et al, 1990 ). A recent study examined the neural correlates of vibration intensity by considering three vibration intensities (0.25, 0.38, and 1.3 g) (Choi et al, 2020 ). Results demonstrated that the maximum and minimum peak, and peak to peak values of somatosensory evoked potential (SEP) patterns in the C3 somatosensory area increased as the stimulus intensity increased.…”
Section: Introductionmentioning
confidence: 99%